2009
DOI: 10.1097/cej.0b013e32832c3882
|View full text |Cite
|
Sign up to set email alerts
|

Effective anti-tumor responses induced by recombinant bacillus Calmette–Guérin vaccines based on different tandem repeats of MUC1 and GM-CSF

Abstract: In this study, we constructed several novel breast cancer vaccines, Bacillus Calmette-Guérin (BCG)-MUC1 variable-number tandem repeats (VNTR) 1/4/8-CSF, that consist of BCG and express 1, 4, and 8 of the tandem repeats of MUC1 and human granulocyte-macrophage colony-stimulating factor (GM-CSF). The ability of the three recombinant BCG vaccines to inhibit breast cancer growth was observed in human (hu)-peripheral blood lymphocyte (PBL)-severe combined immunodeficient (SCID) mice. Prophylactic protective respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…SCID mice reconstituted with human PBL followed by immunization with the rBCG strains developed MUC1-specific cellular immune respnses and enhanced protection against MUC1-positive human breast cancer xenografts compared to control mice reconstituted with human PBL and immunized with non-cytokine secreting BCG. Studies have also www.intechopen.com demonstrated that the antitumor effects of the rBCG strains were correlated with the number of MUC1 tandem repeats delivered by BCG ( a Yuan et al, 2009Yuan et al, , 2010. These results suggest that these MUC1 rBCG strains coexpressing Th1-stimulating cytokines are promising candidates as breast cancer vaccines and thus deserve further investigation.…”
Section: Anti-tumor Studiesmentioning
confidence: 94%
See 3 more Smart Citations
“…SCID mice reconstituted with human PBL followed by immunization with the rBCG strains developed MUC1-specific cellular immune respnses and enhanced protection against MUC1-positive human breast cancer xenografts compared to control mice reconstituted with human PBL and immunized with non-cytokine secreting BCG. Studies have also www.intechopen.com demonstrated that the antitumor effects of the rBCG strains were correlated with the number of MUC1 tandem repeats delivered by BCG ( a Yuan et al, 2009Yuan et al, , 2010. These results suggest that these MUC1 rBCG strains coexpressing Th1-stimulating cytokines are promising candidates as breast cancer vaccines and thus deserve further investigation.…”
Section: Anti-tumor Studiesmentioning
confidence: 94%
“…Most of these cytokine-and chemokine-secreting rBCG strains showed their abilities to enhance BCG-induced cellular immune responses including Th1 cytokine production, cellular cytotoxicity, DC activation, and anti-BCG or anti-M.tb infection. Some of them even showed their antitumor effects in animal models of melanoma (Duda et al, 1995), breast cancer (Chung et al, 2003;a Yuan et al, 2009, Yuan et al, 2010, and bladder cancer (Arnold et al, 2004). Certain cytokine-secreting rBCG strains also induced humoral immune responses and Th2 cytokine production other than cellular immune responses in vitro and in vivo.…”
Section: Th1 Cytokine-secreting Rbcgmentioning
confidence: 99%
See 2 more Smart Citations
“…Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a good adjuvant and immune regulatory molecule, which can be designed as vaccines for cancers and infectious diseases [26,27]. Recombinant GM-CSF stimulates up-regulation of major histocompatibility complex (MHC) class II and co-stimulatory molecules such as CD80 and CD86 on antigen presentation cells (APC) [26].…”
Section: Introductionmentioning
confidence: 99%